The effect of Aureomycin and Sulmet combinations in feed on the performance of cattle - Phar, P.A.; Zimmer, P.R. (Kansas State University. Agricultural Experiment Station, 2011)
Two feedlot trials were conducted during the summer of 1967 at the Morris Feed Yards, Marris, Kansas, to study effects of aureomycin (chlortetracycline) and sulfamethazine fed alone or in combination on weight gain, feed efficiency and general health of newly arrived feeder calves.
Keywords: Beef; Aureomycin; Sulmet; Performance